Glacier-Wide Mass Balance and Compiled Data Inputs: Juneau Icefield Glaciers ... - Christopher J. Mcneil; Seth W. Campbell; Shad R O'Neel; Emily H Baker; Katherine E Bollen (U.S. Geological Survey, 2019)
This data release includes glacier wide mass balance solutions for Taku and Lemon Creek Glaciers, as well as the refined inputs used in these calculations. Input data are of three types: 1) time-variable area altitude distribution (AAD); 2) time series of point water balance at long term sites (with secondary sites given in recent years); 3) weather data from nearby stations, either installed along the glacier margins or taken from a nearby site if continuous glacier-adjacent data is unavailable. The USGS runs a coded analysis to transform the three input data types to the output glacier-wide data. Output data represent surface mass balance estimates. The output solution is a geodetically calibrated, conventional glacier-wide mass balance, which represents our preferred solution. Conventional glacier-wide mass balance from direct observations without calibration can be easily derived by using the geodetic calibration coefficients provided, if desired. We do not explicitly account for basal or englacial ...